2017
DOI: 10.1111/jog.13332
|View full text |Cite
|
Sign up to set email alerts
|

Normal amniotic fluid volume across gestation: Comparison of statistical approaches in 1190 normal amniotic fluid volumes

Abstract: The four statistical methods produced similar results at gestational ages in which AFV was high. The quantile regression approach, however, produces results that are more reflective of the data when the data are sparse. Given the flexibility and robustness of the quantile regression method, we recommend its use in constructing reference intervals when the interest lies in the tails of the reference distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…It remains uncertain whether these interventions would ultimately improve pregnancy outcomes. A systematic review and meta‐analysis confirmed that the AFI identifies more pregnancies with oligohydramnios than SDP, which increases inductions and maternal morbidity without improvements in pregnancy outcomes . Our study adds to the evidence by confirming that the SDP technique is superior for the diagnosis of a low fluid volume.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It remains uncertain whether these interventions would ultimately improve pregnancy outcomes. A systematic review and meta‐analysis confirmed that the AFI identifies more pregnancies with oligohydramnios than SDP, which increases inductions and maternal morbidity without improvements in pregnancy outcomes . Our study adds to the evidence by confirming that the SDP technique is superior for the diagnosis of a low fluid volume.…”
Section: Discussionsupporting
confidence: 61%
“…Sandlin et al initially evaluated the AFVs of 379 normal pregnancies across gestation using quantile regression (QR). That study was followed by a study by Ounpraseuth et al, who compared and contrasted 4 common statistical methods to determine whether one method was better than the others in determining the actual AFV across gestation in 1190 normal singleton pregnancies. All 4 statistical methods produced similar curves at gestational ages when data points were plentiful.…”
mentioning
confidence: 99%
“…It also plays an important role in fetal lung and limb development [ 1 ]. The volume of amniotic fluid varies at different stages of pregnancy [ 2 , 3 ], and the average amniotic fluid volume is 400 mL at term [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also plays an important role in fetal lung and limb development [1]. The volume of amniotic uid varies at different stages of pregnancy [2,3], and the average amniotic uid volume is 400 mL at term [4].…”
Section: Introductionmentioning
confidence: 99%